Study on failure mechanism and control of surrounding rock of inclined strata crossing roadway in deep coal mine - Fang, Wanwei; Li, Mingxin; Huang, Peng; Shi, Taotao; Chen, Yeqiang; Ma, Shijin; Ren, Guohui (Frontiers in Earth Science, 2024)
Abstract：China's coal mines are mainly underground mines, and a large number of roadways have to be excavated underground. It is of great significance for coal mine production to adopt safe and reasonable roadway support methods. In the process of roadway excavation, the rock stratum is inclined and the roadway pass through the layer. Since the surrounding rock conditions of the roadway passing through the layer are more complicated, it is easy to cause deformation of surrounding rock, failure and floor heave, which makes the support work difficult. In order to solve this problem, the mechanical properties of roadway surrounding rock were tested and the failure of roadway surrounding rock was analyzed using the +260 horizontal centralized transportation roadway in Changcheng No.2 mine. The surrounding rock of the roadway was divided into 8 regions, and the stress analysis of the surrounding rock in different regions was carried out. It is found that the left shoulder pit, the right side and the floor of the roadway are prone to damage. The influence of the lateral pressure coefficient, the rock dip angle and the lithology on the failure of the roadway surrounding rock was analyzed by Mohr-Coulomb failure criterion, and the specific failure range of the roadway surrounding rock was obtained. The support optimization design of the roadway was carried out, and the weak area of the surrounding rock was reinforced. The deformation monitoring of roadway surrounding rock after support optimization was carried out. The field monitoring results show that after the optimized support, the displacement of the roof and floor of the roadway section and the two sides are reduced by 43.6 % and 40.8 % respectively compared with the original scheme, and the deformation of the surrounding rock also shows a trend of gradual stability, and the surrounding rock of the roadway is effectively controlled. The research can provide a new way for the stress and failure analysis of the surrounding rock of the inclined rock roadway.